PENGARUH KEMAMPUAN BERPIKIR KRITIS, KEPERCAYAAN DIRI, DISIPLIN BELAJAR, LINGKUNGAN KELUARGA DAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 7 PADANG - Fransiska Gushaeni; Dwinda, Lovelly; Yasmi, Fifi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of critical thinking skills on the learning achievement of class X students in economics subjects at SMA Negeri 7 Padang, the influence of self-confidence on the learning achievement of class X students in economics subjects at SMA Negeri 7 Padang, the influence of learning discipline on the learning achievement of class X students in economics subjects at SMA Negeri 7 Padang, the influence of family environment on the learning achievement of class X students in economics subjects at SMA Negeri 7 Padang, the influence of peers on the learning achievement of class X students in economics subjects at SMA Negeri 7 Padang, the influence of critical thinking skills, self-confidence, learning discipline, family environment and peers on the learning achievement of class X students in economics subjects at SMA Negeri 7 Padang. This type of research is associative research. The results of the study show that: First, there is a significant influence between critical thinking ability (X1) on student learning achievement (Y), with a regression coefficient value of -1.948, t_(count)= -88.502> t_(table)-1.980 and a significance value of 0.000 <0.05, so that Hₐ is accepted and H₀ is rejected. Second, there is a significant influence between self-confidence (X2) on learning achievement (Y), with a regression coefficient value of 0.037, t_(count)= 2.996> t_(table)1.980 and a significance value of 0.003 <0.05, so that Hₐ is accepted and H₀ is rejected. Third, there is a significant influence between learning discipline (X3) on learning achievement (Y), with a regression coefficient value of 0.073, t_(count)= 6.335> t_(table)1.980 and a significance value of 0.000 <0.05, so that Hₐ is accepted and H₀ is rejected. Fourth, there is a significant influence between family environment (X4) on learning achievement (Y), with a regression coefficient value of 1.570, t_(count)= 42.739> t_(table)1.980 and a significance value of 0.001 <0.05, so that Hₐ is accepted and H₀ is rejected. Fifth, there is a significant influence between peers (X5) on academic achievement (Y), with a regression coefficient of -0.042, a t_(calculated) value of -4.159 > t_(table) -1.980, and a significance value of 0.000 <0.05. Therefore, Hₐ is accepted and H₀ is rejected. Sixth, there is a significant joint influence between critical thinking skills, self-confidence, learning discipline, family environment, and peers on the academic achievement of grade 10 students at SMA Negeri 7 Padang.